Prognostic factors in microinvasive cervical squamous cell cancer: long-term results. Issue 1 (1st January 2005) - Raspagliesi, F.; Ditto, A.; Quattrone, P.; Solima, E.; Fontanelli, R.; Dousias, V.; Kusamura, S.; Carcangiu, M. L.
Abstract : We examined tumor-related pathologic factors and cone-related characteristics to identify parameters related to recurrence in microinvasive squamous cell carcinoma of the cervix treated with conization. This is a retrospective study on 67 consecutive cases of microinvasive carcinoma of the cervix [depth of invasion (DI) <3 mm] treated with conization. The mean follow-up was 121 months (range 72–276 months). Four (6%) invasive recurrences were observed. Presence of lymphvascular space involvement (LVSI) was significantly related with recurrences ( P < 0.05). The mean distance between tumor margin and apex of the cone (apical clearance) was 10.6 mm (range 5–22 mm), and the mean distance between lateral border of the cone and tumor margin (lateral clearance) was 6.5 mm (range 1.7–15 mm). We adopted cut-off values of 10 and 8 mm for apical and lateral clearances, respectively. We found a statistically significant difference between apical clearance and recurrence rate ( P < 0.02). The LVSI was, other than DI, an important prognostic factor. Apical clearance was significantly correlated with recurrence. The cone-related characteristics, other than tumor-related pathologic factors, could help the decision concerning the definitive therapy for microinvasive carcinoma of the cervix.